Overcoming neoliberal globalization: social-ecological transformation from a Polanyian perspective and beyond - Brand, Ulrich; Görg, Christoph; Wissen, Markus (Globalizations, 2020)
The ecological crisis has intensified in many respects. Prominent proposals to deal with the crisis are discussed under the header 'sustainability transformations' or even 'Great Transformation'. We argue that most contributions suffer from a narrow analytical approach to transformation ignoring the largely unsustainable dynamics of global capitalism and the power relations involved in it. Thus, a 'new critical orthodoxy' of knowledge about transformation is emerging which runs the danger to contribute to a spatially and socially highly uneven green capitalism. This article claims that the current debate on social-ecological transformation can be enriched by a Polanyian understanding but also based on regulation theory. We distinguish between three types of transformation: incremental adaptation of the current institutional systems, institutional change in favour of a new 'green' phase of capitalism, and a post-capitalist great transformation that implies a profound structural change of the mode of production and living.
Keywords: POLANYI, Karl, 1886-1964; capitalism; crises; debates & debating; ecological crisis; globalization; imperial mode of living; nature as fictitious commodity; regulation theory; social ecology; social-ecological transformation; sustainability

Karl Polanyi on strategy: The effects of culture, morality and double-movements on embedded strategy - Faulconbridge, James R.; Muzio, Daniel (Critical Perspectives on Accounting, 2020)
Karl Polanyi is arguably one of the most significant economic sociologists. At first glance the links between Polanyi’s ideas about markets, society and institutions and strategy may not be obvious. However, there is a hereto unrecognised link between recent writing about institutions and strategy and Polanyi’s work. In this paper we, therefore, chart how, when recognised, these links reveal that Karl Polanyi’s work might provide new ways of thinking about strategy. Our over-riding claim is that Polanyi’s ideas reveal the importance of considering how strategies are defined, responded to, and ultimately rendered effective or ineffective in ways that are determined by relationships between markets, the state and society. It is thus crucial to understand strategy as embedded, this implying consideration of a strategy’s legitimacy in economy and society as an instituted process at any particular place and time. This also implies wider political questions about strategy in society and the extent to which strategists need to be aware of the ‘double movement’ Polanyi discusses and ensure strategies serve the interests of society as well as those of the market.
Keywords: Double movement; Globalization; Law firms; Polanyi; Strategy

Território e Desenvolvimento em Karl Polanyi: uma revisão sistemática - Rodrigues, Waldecy; Camargo, Wainesten (Redes, 2020)
This paper consists of a systematic review of the literature on territorial economic development from the perspective of Karl Polanyi's works. For this, a protocol was created to order the selection of scientific articles, after this step, an analysis of the main works that used Karl Polanyi ideas, on the perspective from territorial development, in a central way in their approaches was performed. The main databases used were SCOPUS, WEB OF SCIENCE and SCIELO, from 1990 to 2018. About 100 (one hundred) papers were found that met the protocol of the systematic review. All these works have been read and their details and characteristics can be found in this text. It was identified that Karl Polanyi has a classical approach to territory, and his most discussed ideas are the double movement, embeddedness, and economic history. The main results point to the strength of Karl Polanyi thought in research on development in several territorial scales, allowing to think these issues in interdisciplinary and plural terms.
Keywords: desenvolvimento; development; systematic review; territorial development; território

A Polanyi-inspired perspective on social-ecological transformations of cities - Bärnthaler, Richard; Novy, Andreas; Stadelmann, Basil (Journal of Urban Affairs, 2020)
Based on a Polanyi-inspired research program, we analyze urban transformations as interrelations between infrastructural configurations, i.e. context-dependent material infrastructures and their multi-scalar political-economic regulations, and socio-cultural modes of living. Describing different modes of infrastructure provisioning in Vienna between 1890 and today, we illustrate how political-economic processes of commodification and decommodification have co-evolved with socio-culturally specific modes of living, grounded in different classes and milieus. We show how, today, two modes of living—“traditional,” established during postwar welfare capitalism, and “liberal,” formed during neoliberal capitalism—co-exist. In the current conjuncture of rising inequality, neoliberal urban regeneration, and accelerating climate crisis, these modes of living are not only increasingly polarized and antagonistic, but also increasingly unable to satisfy needs and self-defined aspirations. Therefore, we explore the potential of social-ecological infrastructural configurations as an alliance-building project for a systemic social-ecological transformation, potentially linking different classes, social segments and forces around a common eco-social endeavor.

Polanyi meets Bolsonaro: Reactionary politics and the double movement in twenty-first-century Brazil - Evans, Peter (International Sociology, 2020)
Twenty-first-century Brazil’s political evolution is a window on the dynamics of contemporary political transitions. The inability of Brazil’s Workers’ Party to sustain its social democratic project and the subsequent rise of the reactionary regime of Jair Bolsonaro are, in turn, part of a global pattern of political change. Karl Polanyi’s vision of the ‘double movement,’ in which the dominance of the market vies with the countervailing movement for social protection, offers an analytical springboard for reflecting on these political transitions. Trying to understand the movement for social protection leads to examining ebbs and flows in the momentum of mobilization. Trying to understand how market dominance leads to reaction brings us back to Polanyi’s advocacy of ‘crass materialism’ as a lens for looking at reaction, and from there to consideration of how the structural power of capital undercuts efforts at social protection and opens the door to reaction.
Keywords: Brasil; Brazil; Brésil; Polanyi; finance; finanzas; protección social; protection sociale; reacción; reaction; réaction; social protection

Re-grounding the city with Polanyi: From urban entrepreneurialism to entrepreneurial municipalism - Thompson, Matthew; Nowak, Vicky; Southern, Alan; Davies, Jackie; Furmedge, Peter (Environment and Planning A: Economy and Space, 2020)
Conventional approaches to local economic development are failing to address deepening polarisation both within and between city regions across advanced capitalist economies. At the same time, austerity urbanism, particularly in the UK, presents challenges for urban authorities facing reduced budgets to meet increased demands on public services. Municipalities are beginning to experiment with creative responses to these crises, such as taking more interventionist and entrepreneurial roles in developing local economies, generating alternative sources of revenue or financialising existing assets. Rooted in a Polanyian perspective and building on the concepts of the entrepreneurial state and grounded city, we identify an embryonic alternative approach – what we call ‘entrepreneurial municipalism’ – as a policy pathway towards resolving enduring socioeconomic problems where neoliberal urban-entrepreneurial strategies have failed. We situate entrepreneurial municipalism as one strand in an assemblage of new municipalist interventions, between radical urban social movements and more neoliberal strategies such as financialised municipal entrepreneurialism. Drawing on original research on the Liverpool City Region, we explore how local authorities are working with social enterprises to harness place-based assets in ways which de-commodify land, labour and capital and re-embed markets back into society. Finally, we draw upon Polanyi as our guide to disentangle differences in approach amongst divergent forms of municipalist statecraft and to critically evaluate entrepreneurial municipalism as a possible trajectory towards the grounded city.
Keywords: Entrepreneurial state; Polanyian economic geography; local economic development; municipal statecraft; urban policy

BRIE Working Paper 2020-6 What Polanyi Teaches Us: The Platform Economy and Structural Change - Eldred, Christopher (The Berkeley Roundtable on the International Economy, 2020)
The welfare system was meant to reduce the 9 vulnerability of citizens to the market, thereby containing the consequences of the market economy and labor commodification. [...] As an adaptation to the consequences of the market, the welfare system is an effort to cushion the effects of the market, not a change its underlying logic of commodification. [...] From this perspective, the political debates about the rules to be applied to the operations of the platform economy are part of the “second movement,” i.e., a reaction to the platform economy. [...] In contrast, to the industrial revolution where the capitalist moved production into the factory to develop greater control than was possible with the putting-out system, the platform extrudes the work and obligations outside the boundaries of the firm. [...] In actuality the relationship between the members of the ecosystem and the platform is hierarchical and based upon an extreme power asymmetry within which the ecosystem members are at the mercy of the platform which controls the nexus of relationships (Cutolo and Kenney, 2020).
Keywords: platform economy; welfare

Capitalismo e lutas sociais: abordagens recentes à articulação entre Marx e Polanyi - Filho, Ricardo Framil (Cadernos CERU, 2020)
The article explores recent contributions that rely on the combination of ideas from Karl Marx and Karl Polanyi to conceptualize social struggles. Two approaches are presented: selective perspectives, which highlighted the differences between class struggles as defined by the Marxist tradition and social reactions theorized by Karl Polanyi’s double movement, and inclusive viewpoints, that emphasized the potential convergence between these different expressions of contestation. Thus, we seek the basic elements of a theory of the structural roots of social struggles in contemporary capitalism. Thereafter, the article explores with greater attention the theories of Michael Burawoy and Nancy Fraser. A comparative reading indicates that this theoretical project is promising because it allows for social struggles to be linked to systemic contradictions, but it also shows that relevant conceptual difficulties persist. The conclusion is that more than a definitive theory, the debates raised by this theoretical outlook suggest central questions for the reflection on labor, classes and capitalist societies at large. O artigo explora contribuições recentes que propuseram a articulação teórica entre ideias de Karl Marx e de Karl Polanyi para conceptualizar as lutas sociais. São identificadas duas abordagens: perspectivas seletivas, que destacaram as diferenças entre as lutas de classes tal como definidas pela tradição marxista e as reações sociais teorizadas pela tese do duplo movimento de Karl Polanyi, e sínteses ecléticas, que enfatizaram a convergência potencial entre essas diferentes expressões de contestação social. Buscam-se, assim, os elementos fundamentais de uma teoria das raízes estruturais das lutas sociais no capitalismo contemporâneo. Explora-se com maior cuidado, então, as teorias de Michael Burawoy e de Nancy Fraser. Uma leitura comparativa indica que essa orientação teórica é promissora porque permite associar as lutas sociais a contradições sistêmicas, mas revela, também, que persistem dificuldades conceituais relevantes. Conclui-se que mais do que uma teoria definitiva, os debates suscitados por essa vertente teórica sugerem questões centrais para a reflexão sobre o trabalho, as classes e as sociedades capitalistas em um sentido amplo.
Keywords: MARX, Karl, 1818-1883; capitalismo; duplo movimento; lutas de classes; lutas sociais

Commodification & countermovement: community-supported agriculture (CSA): a case study in Minas Gerais, Brazil - Matzembacher, Daniele Eckert; Meira, Fabio Bittencourt (Organizações & Sociedade, 2020)
The conventional way of producing and distributing food is based on the use of agrochemicals, fertilizers, industrial fertilizers and other techniques from the Green Revolution, with increasing dependence on financial-industrial capital, which implies the intensification of the agriculture commodification. The object of this study was the emergence of modes of organization resisting this trend. Based on the theoretical reference of Karl Polanyi (2012a, 2012b), a case study was developed in a Community-Supported Agriculture (CSA) initiative. It is a movement that resituates agricultural production through the principles of fair trade, agroecology and the use of short supply chains, which bring production and consumption closer together. The result is a better nutritious quality food at affordable and fair price. The analysis of the CSA Alfa case points to the coexistence of different principles of regulation, in a combination of mercantile exchange and reciprocity. According to the proposition by Karl Polanyi, the economic activity is shown to imbricate with the social aspect, of which friendship, tolerance, fidelity and commitment establish a community ethos around food. The CSA seems to manifest a countermovement to the commodification by enhancing the relative autonomy of individuals that elevates the social cohesion of the participating groups. Resumo A forma que se tornou convencional de produzir e distribuir alimentos baseia-se no uso de agroquímicos, adubos, fertilizantes industriais e de outras técnicas provenientes da Revolução Verde, com crescente dependência do capital financeiro-industrial. Isto significa a intensificação da mercantilização da agricultura. O problema que norteou esta pesquisa é a emergência de modos de organização resistentes a essa tendência. Com base no referencial teórico de Karl Polanyi (2012a, 2012b), construiu-se um estudo de caso cujo objeto é a agricultura sustentada pela comunidade, cujo acrônimo em inglês é CSA (community supported agriculture). Trata-se de um movimento que ressitua a produção agrícola pelos princípios do comércio justo e da agroecologia e uso de cadeias curtas que aproximam produção e consumo. O resultado é um alimento de qualidade nutritiva superior a preço acessível e justo. A análise do caso CSA Alfa aponta a coexistência de diferentes princípios de regulação numa combinação de troca mercantil e reciprocidade. Na esteira de Karl Polanyi, observa-se a atividade econômica imbricada ao social, daí que amizade, tolerância, fidelidade e comprometimento estabelecem um ethos comunitário em torno do alimento. A CSA parece manifestar um contramovimento à mercantilização ao potencializar a autonomia relativa dos indivíduos, o que eleva a coesão social dos grupos participantes.
Keywords: Karl Polanyi; commodification; community-supported agriculture; reciprocity; social cohesion

현대 사회적경제의 기원에 대한 시론: Karl Polanyi의 경제사상으로부터 - 권병욱; 이준우 (사회적가치와 기업연구, 2020)
본 논문은 최근 대중적 관심을 불러일으키는 사회적경제를 주목하여 그 이론적 기원을 탐색하기 위한 목적을 가지고 있다. 이 작업은 다수의 연구자들과 활동가들에게 사회적경제에 대한 이해의 지평을 넓히고 보다 풍부하게 사회적경제에 대한 접근의 근거를 제공할 것이다. 다양한 분야에서 어려움에 직면하고 있는 우리 사회의 현실을 감안할 때, 새로운 대안경제로 사회적경제의 타당성 차원에서도 필요한 작업이다. 실제로, 기존 경제학은 합리적인 인간을 전제로 자기조정적인 시장메커니즘에 의한 이윤 극대화논리를 발전시켜 왔다. 가격을 매개로 시장의 무오류적 완결성을 고착해 온 것이다. 그러나 시장이 적절하게 기능하지 못하고 정부의 개입에 의해 해결되지 못한 다양한 사회문제들에 직면하면서 인간의 발전과 자연의 성숙을 도모하는 새로운 사회적경제의 가능성이 중시되고 있는 실정이다. 이러한 관점에서 본 연구는 주류경제학의 오류와 현대 경제에 대한 폴라니의 비판을 근저에 두고 그가 주목했던 두 명의 혁신적 사상가, 존 벨러스와 로버트 오웬을 통해서 사회적경제의 기원과 본질을 밝히고 그것이 감당해야 할 몫을 분명히 하고자 한다. KM - english title: A Study on the Origin of the Social Economy in Modern Society: Based on Karl Polanyi’s Economic Ideology
Keywords: BELLERS, John; OWEN, Robert; mutual aid; poverty; publicity; reciprocity; social capital; social economy; social enterprise; solidarity

Requisitos para el cambio transformativo: contribuciones de Karl Polanyi - Kirby, Peadar (International Review of Economic Policy-Revista Internacional de Política Económica, 2020)
Una pregunta clave que surge de la pandemia de coronavirus es qué se requiere para hacer de esta fase temporal un camino hacia el cambio transformador. O, como sucedió en gran medida después de la crisis financiera de 2008, ¿volverá la sociedad a una economía dominada por el crecimiento y cargada de carbono basada en una ética del individualismo radical y el consumismo desenfrenado, informada por recetas neoliberales? Este artículo se basa en el trabajo de Karl Polanyi (1886-1964) para ofrecer un marco teórico alternativo para guiar el cambio social transformador en la era del cambio climático. Comienza por identificar una característica clave del equilibrio entre la estructura y la agencia en la sociedad contemporánea, a saber, un optimismo tecnológico y propone un marco alternativo a través de la economía política. La segunda sección identifica los dos marcos teóricos clave que informaron las configuraciones dominantes de la economía política desde la Segunda Guerra Mundial: un marco socialdemócrata y un marco neoliberal. Se argumenta que ahora es necesario un nuevo marco. La tercera y más larga sección dibuja una gama de contribuciones conceptuales de Polanyi para ofrecer una teoría distintivamente diferente a la que ofrece el neoliberalismo. Estos incluyen: sociedad de mercado; diferentes significados de economía; mercancías ficticias; formas de integración; doble movimiento; descubrimiento de la sociedad; la persona humana y la libertad; y el poder de la tecnología. La sección final saca conclusiones.
Keywords: COVID-19; climate change; market society; neoliberalism

Karl Polanyi contre Ludwig von Mises - Pinault, Santiago (Austriaca. Cahiers universitaires dʼinformation sur lʼAutriche, 2020)
Les analyses de Felix Schafer, alors le plus proche collaborateur de Karl Polanyi (1886-1964), permettent de comprendre un débat entamé en 1922 à Vienne entre Polanyi et Ludwig von Mises (qui était alors le représentant le plus célèbre de l’école autrichienne). Les enjeux de leur opposition devaient structurer la pensée polanyienne en son entier. Dans les décennies suivantes, notamment les années 1940-1950 aux États-Unis, c’est en esquissant une approche de type sociologique que Polanyi allait paradoxalement élaborer, sur des catégories conjointes qu’il tire indissociablement de Max Weber et de Carl Menger, un paradigme que nous qualifions de « vieux (ou vétéro)-autrichien » en raison de son retour aux sources de cette tradition (prise au sens large). Le formalisme de Mises s’y intègre pour former une « branche formaliste » selon Polanyi, qui nous a peut-être laissé là sa plus féconde intuition.
Keywords: Austria; MISES, Ludwig von; WEBER, Max, 1864-1920; substantivisme

The Euro as a Polity: Karl Polanyi in Frankfurt? - Thomasberger, Claus (Global Perspectives, 2020)
As factors of production, labor, money, and land play a role in economics that is rarely understood. The difficulty of deriving the contribution of the individual factor of production to the value of jointly produced final commodities (the famous “problem of imputation”) occupied generations of Austrian economists (Hayek 1984) and inspired Ludwig Mises to produce his 1920 article “Economic Calculation in the Socialist Commonwealth” (Mises 1935). Any attempt at rational socialist planning is utopian, Mises argued, because only price-making markets for the factors of production provide the information for economically rational decision-making. If the birthplace of neoliberalism was, as Slobodian (2018, p. 30) put it, Ludwig Mises’s office in the Vienna Chamber of Commerce, this article was its moment of birth.Karl Polanyi was one of the first to respond, doing so in the same journal in which Mises’s piece had been published, the Archiv für Sozialwissenschaften, long before Friedrich Hayek, Walter Lippmann, Lionel Robbins, and German ordoliberals such as Alexander Rüstow and Wilhelm Röpke intervened (Polanyi 2016, 2018b). In his contributions to what became the famous socialist accounting debate, Polanyi outlined his idea of a society’s “constitutional form … as a relationship of mutual recognition” (Polanyi 2018a, 54) based on direct cooperation between consumers and producers, as well as a functional democracy.Two decades later, Polanyi resumed this discourse with a more radical critique, making use of Mises’s argument for his own end (cf. Thomasberger 2020). Mises’s case for price making markets is no less utopian than the central planning model, he argued in The Great Transformation (TGT). The crucial point, Polanyi contended, is that the factors of production are fundamentally different from genuine commodities. Polanyi drew on a line of reasoning put forward by the sociologist Ferdinand Tönnies (2001, p. 81-82) and by Mises’s intimate enemy, the Austrian economist Friedrich Wieser (1927, p. 175-77), who was inclined toward Fabian socialist ideas. Given that the factors of production are not (and cannot be) produced for sale by private enterprises, the commodity form of labor, money, and land is fictitious.Polanyi’s category fictitious commodities is the pivot of Klein’s paper. This starting point allows him to go beyond the common interpretation of Polanyi’s work, which focuses on the dichotomy of market opening and social closure, and to address instead a more profound problem: the conflict between capitalism and democracy. Such a reading is indeed closer to the core of the Polanyi approach, which refers to a society that “transcends the self-regulating market by consciously subordinating it to a democratic society” (Polanyi 2001, 242). Not social protection, but democracy, is the alternative to the self-regulation of the market. Polanyi never believed that protection could achieve more than a temporary stabilization of market society. In fact, it is somewhat paradoxical that in the discussion about the contradictions of European integration, Polanyi is celebrated as a defender of societal closure, while he himself expressed the conviction that the protective measures “impaired the self-regulation of the market, disorganized industrial life … and finally disrupted the social organization based upon it” (Polanyi 2001, 4). From the point of view of the conflict between capitalism and democracy, the institutions that result from the attempt to commodify labor, money, and land are crucial because they are, as Klein puts it, the “point of entry of political power into the economic sphere” (Klein 2020, 11). Concerning the debate about the crisis of European integration, this is a rather unexplored terrain.In what follows, I will not discuss the question of whether the category fictitious commodities can be fruitfully linked to the idea of premodern modes of economic integration, a connection that Polanyi himself never established. Instead, I will concentrate on two issues that Klein’s paper raises without discussing them explicitly. The first question is: What if the creation of a self-regulating market system becomes the dominant political goal? What if, for example, the central bank is transformed into a market maker for money on political grounds? The second point seems to me even more important. Europe is not a nation. However, “in Polanyi’s schema, the self-regulating market was a national economic institution” (Polanyi-Levitt 2013, 89), which linked the “rest of the world” to England by a “golden straightjacket,” as Polanyi’s daughter, the development economist Kari Polanyi Levitt, remarked. In TGT even European colonialism plays only a marginal role. As a result, European integration after World War II raises issues that Polanyi did not discuss in depth. I will proceed in two steps: First, I will reconstruct some essential points of Polanyi’s analysis. Following this, I will pose the question of how to apply his analysis to Europe.From the point of view of a market system, the crux of the factors of production—or the fictitious commodities, as I shall hereinafter refer to them—is that, on the one hand, private enterprises must be enabled to buy labor, land, and money on a market. On the other hand, private companies are notcapable of producing and selling the fictitious commodities. The difficulty is obvious: In a market economy, enterprises depend on markets for the fictitious commodities, but such an economy is unable to produce them. This means that the market system depends on external forces. Certainly, this is also true for other institutions and social infrastructures that only the state can provide. However, the fictitious commodities are different in that they cannot be understood as part of the extra-economic framework. Labor, money, and land are economic factors; they are the condition sine qua non of the market system. No self-regulation is conceivable without including the fictitious commodities. What legal scholars with regard to the secular state call the Böckenförde dilemma in the case of fictitious commodities affects economic liberalism directly. The market system is unable to produce and reproduce itself spontaneously. The economic mechanism lives by prerequisites it cannot create. Social institutions are required to provide what for the functioning of a market system is indispensable. Only society can provide the commodities on which a market economy is based. Therefore, in a market society, the economy is not—and can never be—a functional machinery. “Laissez-faire economy was the product of deliberate State action,” as Polanyi (2001, p. 147) stated, summing up the nineteenth-century answer to the dilemma. The different institutions that coordinate economic activities are the outcome not of functional pressure but of a political struggle around the (de)commodification of the fictitious commodities. “Market economies are polities,” to paraphrase the felicitous title of a book edited by Christian Joerges, Bo Stråth, and Peter Wagner (2005).In other words, an ideal market society presupposes the political creation and regulation of particular social institutions whose purpose is to simulate market conditions. Unemployment insurance, health care, union legislation, central bank acts, land property rules, and environmental regulations are indispensable for transforming labor, money, and land into commodity-like entities. Here a conflict between the social nature of the task and its economic role arises. From the perspective of the market system, these institutions fulfill the function of market makers. However, from the viewpoint of society, they allow for various forms of political regulation and economic planning, taking into account the social needs of the different strata of society. It is this tension between their political roots and their economic function within the market system that puts these institutions at the center of the political struggle. Since law cannot ignore prevailing ideals, worldviews, and external expertise, it plays a contradictory role in this process, functioning as a vehicle for commodification and political regulation.In TGT Polanyi showed that from the beginning, law played a key role in the process of commodification. In England, three legal regulations were crucial:Even if a market society presupposes the commodification of all three fictitious commodities, for reasons of space I will concentrate on money. The crucial point is to understand that the nineteenth-century gold standard was primarily not an economic but a political system.In the first decades of the century, substantially inconvertible paper money circulated in England. The commercial banks—and their theoretical advocates, the so-called Currency School—pushed for the right to provide money according to the banks’ calculations. In contrast, the supporters of the Banking School argued that this would lead to the risk of an overissuance of notes. The essential feature of the banking system created by the abovementioned Peel’s Bank Act was to keep the supply of money artificially scarce by linking the amount of banknotes to the quantity of gold in the issuing department of the Bank of England (BoE). By law, political control and the discretionary influence of the government on money and banking were reduced to a minimum.Over the course of the century, the commodification of labor, money, and land in England set in motion a transformation on a global scale. Relying on bank money, the market system generated a previously unknown social and economic dynamic. In the last decades of the “long” nineteenth century, Polanyi (2001, p. 136) commented, “a new way of life spread over the planet with a claim to universality.” The international gold standard gave birth to a worldwide system, in which the constitutional regimes became almost the corollary of the gold standard.Here we can observe in outline two problems that we encounter again in Europe today: (1) Given the legislation that forced central banks to limit the supply of money, the international gold standard not only limited the British government’s room for maneuver, but it confined also, and often even more strictly, the policy space in the other countries. The open market for money and finance created international economic and political interdependencies, which reached deeply into society and undermined democratic aspirations. Social legislation, labor unions, and budgetary and monetary policy were forced to accept the priority of the external monetary stability even if this was in contradiction to national interests. (2) The variety of socioeconomic environments, institutional traditions, and sociopolitical objectives in different countries was negated. The gold standard forced the individual countries to adapt to the liberal economic model with its universal aspirations.The BoE functioned as the conductor of the global monetary orchestra. Polanyi introduced two categories to describe the international dependencies in this period: “anarchistic sovereignty and ‘justified’ intervention in the affairs of other countries” (Polanyi 2001, 261). On the one hand, sovereignty was “anarchistic” insofar as under the gold standard and the prevailing system of unregulated foreign trade, governments lacked any power with respect to international economic affairs. The treatment of trade as a relationship between private undertakings made effective international (political) economic cooperation between states impossible. On the other hand, interventions were “justified” whenever the budgets, finances, and currencies of debtor countries required control. Given the rigidities of the economic system, Polanyi underlined that “the peoples of the world were institutionally standardized to a degree unknown before” (Polanyi 2001, 261).At the same time, however, the inelasticity of the gold supply resulted in a deflationary bias that spread over the world. Even if central banks tried to introduce some doses of flexibility, the system required the adjustment of wages and prices to the current account balances, affecting both the opportunities for profit and the living conditions of large sections of the population. Such a rigid system could survive, Polanyi summarized, only as long as popular democracy was suppressed. Confronted withIn nineteenth-century England, the gold standard and popular democracy were irreconcilable. This explains why attempts to restore the former in the 1920s were bound to fail. Barry Eichengreen took up Polanyi’s point when he pointed out that after the First World War, “the spread of universal suffrage and … the consequent politicization of the policy environment … had destroyed the viability of the gold standard itself” (Polanyi 2001, 233–34). As long as prosperity prevailed, the conflict could be contained. Not so in crisis situations. The restored international gold standard collapsed in 1931.The European Monetary Union (EMU) is at the heart of current debates on the crisis of European integration. Whether Streeck (2014, p. 185) calls the EMU “a political mistake” or Habermas (2012, p. 3) criticizes the “construction flaw of a monetary union,” they share a focus on the Maastricht process. Obviously, this interpretation ignores the fact that the crisis also includes countries—among others the United Kingdom, Poland, and Hungary—that have never been part of the EMU.If we look at the crisis from Polanyi’s perspective, the focus shifts. Not the EMU but the Single European Act, signed in 1986, emerges as the turning point. The single market program was by no means the deregulatory exercise that the European Commission had presented it as being. It was about developing competition throughout the European Union, including markets for labor, land, and money. The novel feature of the program was that it aimed at creating cross-national markets for the fictitious commodities between democratically constituted countries. This is not to say that markets for genuine goods do not cause interdependencies; however, the political character of the process of commodification of the fictitious commodities produces interdependencies of a different quality. Economic, monetary, fiscal, income, and social policy decisions in one country affect directly all other countries participating in the single market. They create political interdependencies, which, if we take Habermas’s understanding that “democratic self-government means that the addressees of mandatory laws are at the same time their authors” (Habermas 2012, 14), is incompatible with national democracy.Why did Jacques Delors and the European Commission nevertheless argue for the creation of Europe-wide markets for the fictitious commodities? Did they underestimate the political costs? Or did they believe that the economic benefits outweighed the loss of political self-determination?It is important to keep in mind that the discussions within the economic discipline never led to the consensus that the European Commission assumed. David Ricardo (1817) had already argued that markets for production factors are by no means necessary in order to enjoy the advantages of the international division of labor. In the twentieth century, declared supporters of free trade such as Gottfried Haberler (1930) and Jagdish Bhagwati (1998) took the same line. Recently, an IMF Staff Paper evaluating empirical studies on the effects of financial globalization concluded that there is evidence not of direct economic gains but rather of political effects: “Our interpretation of the newer literature is that … financial openness can … impose discipline on macroeconomic policies” (Kose et al. 2009, 10). In Europe, the internal market program was met with strong approval by the neoliberal camp. It is reasonable to assume that with the single market, Europe made the political turnaround that the Anglo-Saxon world had already accomplished with Thatcher and Reagan.Be that as it may, the commodification of labor, land, and above all money changed the rules of the game.1 To remain within the context of monetary relations: Open financial markets transformed the European Monetary System (EMS) into an arrangement that came close to what McKinnon (1988) had defined as the “gold standard without gold.” Although the EMS was intended as a symmetrical arrangement, under the conditions of open financial markets the most hard-nosed national central bank, the Deutsche Bundesbank (DBB), assumed the role of a kind of European central bank. The monetary authorities of other European countries were forced to adapt. Recall that in autumn 1992, the conflicts that arose out of these political dependencies nearly put an end to European monetary integration. The different conditions—most European countries were in recession, while Germany was experiencing the unification boom—placed incompatible demands on monetary policy. In this conflict, the DBB acted not as a European but as a German central bank, raising interest rates to record levels. In September 1992, the system faltered. The Italian lira and the pound sterling were forced out of the exchange rate mechanism. Great Britain definitively turned its back on monetary integration, while in Italy a political earthquake shook the party-political landscape.Streeck (2014, p. 186) calls for “a new European monetary system” built on Keynes’s model of fixed but adjustable exchange rates. Now, Keynes was well aware of the fact that systems such as the Bretton Woods System (or the original EMS) are incompatible with transnational financial markets.2 They can function only as long as capital movements are politically controlled. The internal market program destroyed these conditions.Fatally, the Maastricht Treaty did not pursue the goal of reducing political interdependencies but was limited to replacing asymmetry with the all-encompassing dependence on a supranational, technocratic institution that is apparently separate from the political sphere. The German economist Horst Sievert (1993, p. 18) exposed the core idea of the EMU when he remarked, “What is decisive, is that in the monetary union the individual state must pay its debts with money that it cannot produce itself.”3 In the European type of monetary union, not the political authorities but technocrats and private financial institutions control the currency in which public debt is denominated. While in countries with their own currencies the government can turn to its central bank in a time of need, in the EMU, as we have seen in the case of Greece, state bankruptcy becomes a real threat.The financial and economic crisis has revealed the utopian character of the idea of imposing discipline through markets. To touch on just two aspects: (1) Since then, the socioeconomic heterogeneity between the countries has found new forms of expression. By creating long-term interest rate differentials, the crisis has spatially divided what was conceived as a single European capital market. Paradoxically, those countries most dependent on cheap credit are penalized by less favorable financing conditions. (2) If the demand for money and credit is insufficient, efforts to keep the money supply scarce lose their purpose. Neither the Public Sector Purchase Program (PSPP) adopted in 2015 nor the Pandemic Emergency Purchase Program (PEPP) can be derived from theoretical principles based on the commodity fiction of money. The coronavirus crisis is, as Peter Bofinger (2020) suggests, “the hour of Modern Monetary Theory”—an approach that until recently was marginalized by mainstream economics because it regards money not as a commodity but as a means of payment.To overcome the crisis of European integration, two alternatives are usually proposed: deepening integration, “an ever closer union,” or downscaling of integration, defending democracy on the nation-state level. More than seven decades ago, Polanyi already envisaged a third possibility: political cooperation between self-determining nations. Polanyi was in favor of (a) the international division of labor and (b) the liberty of the individual countries “to organize national life at will” (Polanyi 2001, 262). He was (c) aware that both could be achieved only if the commodification of labor, money, and land was restricted. His ideas were indeed aimed at politically controlled regional cooperation between countries that would maintain and develop their particular characteristics. In the final chapter of TGT, he highlighted:The link between the removal of the fictitious commodities from the market and the emergence of a variety of new societies is the crucial point. In another well-known essay published shortly after TGT, Polanyi outlined his idea of a global economic order by contrasting his concept of “regional planning” with that of “universal capitalism” (Polanyi 2018b). For Polanyi, a variety of human societies was not only a fact but also a normative value. It must suffice here to recall his last project, the magazine Co-Existence, which explicitly aimed at the strengthening of peaceful international cooperation.4From this perspective, the debate on the ECB cannot be limited to questions of Outright Monetary Transactions, negative interest rates, state financing, and price stability. The question of how the monetary authorities of a heterogeneous European Union can and should act has to go back to the root problem, the commodification of money. To bring Polanyi’s ideas to Frankfurt would mean at least:However, from the point of view of the commodity fiction, the erosion of the predominance of formal legal rules in the mid-1980s, the emergence of the “regulatory state,” the turn toward governance, and finally the spread of “executive managerialism” (Joerges and Weimer 2013) since the financial crisis appear as a series of functionally necessary adjustments to an originally incomplete regime. As long as this vision prevails, the tensions between increasingly technocratic rule and democratic control are likely to persist. In the light of Europe’s ever-growing diversity, a fundamental redesign of the project, including a reconceptualization of European law that overcomes the fiction of an apolitical integration process, is necessary and, indeed, overdue. Polanyi’s analysis can provide the economic and sociological premises for such an endeavor. However, his writings also show that, especially in the twentieth century, social transformations that would have been necessary proved impossible to implement. We should be prepared; the possibility of some kind of “fundamental shock” to the integration project cannot be ruled out.Claus Thomasberger is a sociologist and economist whose main fields of research are political philosophy, history of economic thought, international political economy, European integration and social ecological transformation. Until 2017, he was Professor of Economics and Foreign Economic Policy at the Berlin University of Applied Sciences. He has been a visiting Professor at the University of Knoxville, the Duke University, and the Vienna University of Economics and Business. He is a member of the Board of the Institute for Ecological Economy Research, Berlin, the International Karl Polanyi Society, Vienna, and of the Executive Committee of the Karl Polanyi Institute of Political Economy, Montreal. Among his publications are: Chronik der großen Transformation, Artikel und Aufsätze von Karl Polanyi 1920-1947 (3 vol.) (with M. Cangiani and K. Polanyi Levitt), 2002-2005; Der neoliberale Marktdiskurs (with W. Ötsch), 2009; Das neoliberale Credo, 2012; Auf der Suche nach dem Ökonomischen (with R. Lucas and R. Pfriem), 2018; Karl Polanyi’s Vision of a Socialist Transformation (with M. Brie), 2018; Karl Polanyi. Economy and Society. Selected Writings (with M. Cangiani), 2018.

The Contemporary Relevance of Karl Polanyi to Critical Social Enterprise Scholarship - Roy, Michael J.; Grant, Suzanne (Journal of Social Entrepreneurship, 2020)
The importance of the work of Karl Polanyi to social enterprise scholarship is often maintained. However, explanations as to how and why his ideas are so relevant to the field are still relatively scarce. In this essay, we argue that engaging with Polanyi’s work directly, and Polanyian scholarship more widely, can provide a deep understanding of the underlying assumptions within current social enterprise conceptualizations, and provide insights into how the relative positioning of market and society may be manipulated to maintain hegemonic positions. Three of Polanyi’s key concepts are considered and discussed in turn: the ‘substantive economy’, the notion of ‘embeddedness’, and his ‘double movement’ thesis. The contemporary relevance of each concept, and the implications for future research, are presented and discussed, with a view to providing a platform from which to pursue a reinvigorated, emancipatory critical research agenda.
Keywords: Polanyi; Social enterprise; critical research; critical social enterprise scholarship; double movement; economic sociology; embeddedness; social business; social enterprise; social innovation; substantive economy

Embedding the atom: Pro-neoliberal activism, Polanyi, and sites of acceptance in American uranium communities - Malin, Stephanie A.; Alexis-Martin, Becky (The Extractive Industries and Society, 2020)
In North America, uranium workers are fighting for their right to participate in a free-market system that provides them with small personal benefits. These workers experience powerlessness, instability, and unpredictability – or social dislocation – by living amidst capitalism’s polluted ecosystems, unstable economies, and disintegrating communities. However, they feel reliant on uranium for their livelihoods and strongly support the industry’s renewal and form sites of acceptance to support industry renewal. Here, we explore the phenomenon of pro-neoliberal activism emerging in communities that identify with uranium markets and that trust in corporate self-regulation, private transparency, and the perceived benefits of potential economic development. Polanyian theory helps us analyze these curious socio-environmental outcomes. While social movements might be ‘progressive,’ ‘regressive,’ or otherwise diverge, Polanyi consistently characterized double movement activists as protecting communities and ecosystems from unstable, self-regulating market systems. But here we see something different and ask: First, how does pro-neoliberal activism contribute to the embedding and institutionalization of neoliberal regimes in uranium mining communities? Second, what structural mechanisms precede and help to facilitate socio-cultural support for free markets and corporate self-regulation, as opposed to support for re-embedding markets in local, public social protections for the US uranium industry?
Keywords: double movement; environmental justice; pro-neoliberal activism; uranium

Karl Polanyi and substantivism in economic development - Rodrigues, Waldecy; Santos, Nayara Silva Dos (Brazilian Journal of Political Economy, 2020)
ABSTRACT A reading of Karl Polanyi’s work gives us a broader and more plural view of the development process beyond the exclusively economic dimension. This scientific text aims to recover the theoretical contribution of Karl Polanyi and its contribution to the understanding of the development process from a plural and substantive conception of economy. The key lesson learned in this research is that regardless of a country’s economic system, one should pay attention to the existing institutional variety and complexity of its cultural and social mosaic. True development will only be achieved if it is structured with effective public policies in order to promote this heterogeneity to the maximum possible social welfare.
Keywords: Economic development; Karl Polanyi; plural economy

Permanenter Notstand und der Kampf um gute Sorge(arbeit) – Polanyi’sche Doppelbewegungen in der Marktgesellschaft - Décieux, Fabienne; Becker, Karina; Kutlu, Yalcin (Industrielle Beziehungen, 2020)
Der Artikel untersucht kollektives Interessenhandeln in der (Klein-)Kinderbetreuung in Deutschland und Österreich. Mit der Polanyi’schen Figur der Doppelbewegung werden die Dynamiken der aktuellen Aushandlungen im Feld der Sorge und Sorgearbeit aufeinander bezogen und analytisch gefasst. Die Bewegung in Form einer (Quasi-)Vermarktlichung steht im Spannungsverhältnis zum ausgeprägten Berufsethos der ErzieherInnen, um das sie durch Proteste (Österreich) und Streiks (Deutschland) kämpfen.
Keywords: (Early) Child care; (Klein-)Kinderbetreuung; (Quasi-)Vermarktlichung; (quasi) marketization; D63; Industrial Relations. JEL: B54; Industrielle Beziehungen; J81; Polanyi; Sorgearbeit; care work

On the Nature of the Countermovement: A Response to Stuart et al.’s ‘Climate Change and the Polanyian Countermovement: Carbon Markets or Degrowth?’ - Carton, Wim (New Political Economy, 2020)
In a recent article for this journal, Stuart, D., Gunderson, R., and Petersen, B. [(2017). Climate change and the Polanyian counter-movement: carbon markets or degrowth? New political economy, 1–14. doi:10.1080/13563467.2017.1417364] discuss solutions to climate change in terms of Karl Polanyi’s concept of the double movement. They set up their argument as a critique of my own article on the topic to make the point that carbon markets do not constitute a genuine form of such countermovement. I’m sympathetic to the critique of carbon markets that the authors present, as well as their discussion of degrowth, which mirrors a by now extensive literature demonstrating the pitfalls respectively the necessity of these diametrically opposed approaches to the current socioecological crisis. However, in setting up their case the authors provide an overly optimistic reading of Polanyi that I believe misses a crucial part of his argument, a reading that at least partly explains our differences in opinion. This commentary offers a friendly critique of Stuart et al.’s use of Polanyi and clarifies the argument in my previous text that the authors take issue with.
Keywords: Polanyi; carbon markets; climate change; commodification; countermovement

Polanyi, Callon, and Amazon: Institutionalist, ANT, and DRAN Approaches to Platform Economies - Caliskan, Koray (Sociologica, 2020)
Drawing on a detailed analysis of Grabher and König’s study of platformization (Grabher & König, 2020), this essay develops a revision of Actor-Network Theory by proposing how a Device, Representation, Actor and Network or a DRAN Approach can be more helpful in making sense of platform economic processes. First, it locates the ways in which Grabher & König’s article approach platforms from an updated Polanyian perspective. Second, it elaborates on how the aforementioned article critiques static Polanyian perspectives while at the same time building a double tension by a) not being clear whether we observe "the platform economy" as an object or platform economization as a process, and b) not paying sufficient attention to how platforms that draw on intangible materialities move beyond being mere marketization relations. Third, it presents how to address these tensions by drawing on novel theoretical advances of DRAN Approaches and fresh empirical research concerning platform economies, located at the intersection between computer science and social sciences. Proposing a possibility to integrate historical and contemporary studies of economic processes, the essay ends by elaborating on how Grabher & König’s article has a potential to enable a multi-perspective dynamic research strategy in making sense of not only the contemporary working of platforms, but their historical and socio-technical condition of possibility.
Keywords: CALLON, Michel; Platform economy; Polanyi; actor-network theory; platform

Destructive Automatism in Modern Societies in Karl Polanyi - De Carolis, Massimo (Politica & Società, 2020)
The concept of “Polanyi’s momentµ should be applied not only to point out some general analogy between today’s economic and social crisis and the one which occurred between the two World Wars and provoked the breakdown of European liberal society. In fact, Polanyi’s work allows us to hypothesize a much deeper continuity between the two crises, where both represent different stages of the same interregnum, the same process of institutional metamorphosis. It hereby helps us to decode the deep structures and the lines of evolution of the whole process. This article argues that the key to such institutional metamorphosis is to be sought in the increasing automatism of modern institutional mechanisms. While such increasing automatism is usually portrayed as technical progress, Polanyi uncovers its ambivalent significance and potential destructiveness for social life.
Keywords: automatism; crisis; institutional mechanism; interregnum

Economía de mercado, globalización y migración: retos y rostros de las personas vulneradas globales. Un análisis desde Karl Polanyi - Franco, Jefferson Frenel Junior Pierrelus (Contextualizaciones Latinoamericanas, 2020)
Este ensayo pretende demostrar cómo el mercado autorregulado que pregonael neoliberalismo es una falacia y que tiende tarde que temprano a acabar odestruir las propias condiciones sociales, ambientales y culturales que aseguranla vida en el planeta. Basado en una globalización financierista, en la privatización yen la liberalización de mercado, ese modelo se ha convertido en la mayor fábrica deempobrecidos, logrando cooptar y subordinar a los Estados a sus designios a travésde las grandes empresas transnacionales e instituciones económicas internacionales.La neo-esclavitud, la miseria, la precariedad y la violencia se han instalado como unmodo de ser y de vivir, aunadas a la emigración, debido a esa explotación, extracciónde recursos naturales a ultranza que lleva a cabo ese modelo económico imperante.Hay voces, manifestaciones, como la de Karl Polanyi, que quieren poner un freno a esemolino satánico, llamado neoliberalismo.
Keywords: economía de mercado; globalización; globalization; market economy; migración; violence; violencia

State Formation, Habitus, and National Character: Elias, Bourdieu, Polanyi, and Gellner and the Case of Asylum Seekers in Ireland - Loyal, Steven; Quilley, Stephen (Historical Social Research, 2020)
Synthesizing material derived from Norbert Elias, Pierre Bourdieu, Karl Polanyi, Max Weber, Benedict Anderson and Ernest Gellner, in Part I the concept of “national character” is delineated as a special case of “habitus” relating to the socio-spatial scale of the nation state. In relation to problems of state-formation, national character is shown to be a figurational and co-developmental function of the system of nation-states in which patterns of mutual identification and “imagined community” involve both the coercive codification and internalization of particular national narratives and origin myths which define “people like us” in terms of a symbolic family; and also, in relation to competing nation-states, the projection and internalization of national group charisma and shame. In Part II, these ideas are applied to the pattern of state formation in Ireland and the recent history of the reception, cultural accommodation, and treatment of asylum seekers.
Keywords: BOURDIEU, Pierre, 1930-2002; ELIAS, Norbert; Ireland; Irishman; Kultur; Sozialpsychologie; Staatenbildung; culture; figuration; habits; habitus; nation; national identity; national stereotype; nationale Identität; nationales Stereotyp; social psychology; state formation

The Moral Economy of the Capitalist Crowd: Utopianism, the Reality of Society, and the Market as a Morally Instituted Process in Karl Polanyi’s The Great Transformation - Somers, Margaret R. (Humanity: An International Journal of Human Rights, Humanitarianism, and Development, 2020)
In an age of egregious inequality and rising authoritarian, many call for a new “moral economy” and turn to Karl Polanyi’s The Great Transformation for inspiration. Yet Polanyi’s great insight is that those who cannot reckon with the moral economy of “market justice”—the claim that market outcomes, however unequal, are morally just—fail to understand the power of capitalism. Justified by its original claim to rest on natural science, market justice laid the predicate for democracy as mortal threat. Polanyi reveals market justice as based not on natural law but on predistributive political power, and builds his democratic socialist vision on the “reality of society.”
Keywords: market justice; moral economy